2020
DOI: 10.1016/j.joep.2019.102196
|View full text |Cite
|
Sign up to set email alerts
|

Childhood exposure to the Second World War and financial risk taking in adult life

Abstract: Adverse childhood experiences might have long-lasting effects on decisions under uncertainty in adult life. Merging the European Survey on Health, Ageing and Retirement with data on conflict events during the Second World War, and relying on region-by-cohort variation in war exposure, we show that warfare exposure during childhood is associated with lower financial risk taking in later life. Individuals who experienced war episodes as children hold lessand are less likely to holdstocks, but are more likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…Can we also see a similar relationship with support of strong defense as in the case of the impressionable years for other age cohorts? This analysis is motivated by findings of Bellucci et al (2019) who argue that exposure to warfare in early life shapes human capital outcomes in later life and has a long-term impact on social preferences.…”
Section: Datamentioning
confidence: 99%
“…Can we also see a similar relationship with support of strong defense as in the case of the impressionable years for other age cohorts? This analysis is motivated by findings of Bellucci et al (2019) who argue that exposure to warfare in early life shapes human capital outcomes in later life and has a long-term impact on social preferences.…”
Section: Datamentioning
confidence: 99%
“…The investigation indicated significant positive impacts of investment behaviours, for instance, years of investment experience as well as the type of investors to trading frequency during the pandemic. In addition, a study by Bellucci et. al (2020) also examined the social crisis impact on FRT.…”
Section: Socialmentioning
confidence: 99%
“…Malaysian (Chin, 2021) Covid-19 pandemic positively impacts investment behaviours in trading frequency. Europe (Bellucci et. al, 2020) Adults who were exposed to WW2 during childhood have lower FRT and are less likely to invest in stocks.…”
Section: Socialmentioning
confidence: 99%
“…A study based on a representative sample of adults from 14 European countries demonstrates that early-life exposure to WW2 increases individual resilience and optimism about life, leading to a higher probability of survival (Arpino et al 2019). Bellucci et al (2020) use the European Survey on Health, Ageing, and Retirement to show that war-exposed individuals have higher resilience to shocks and increased perception of uncertainty and uncontrollability of the environment. Cassar et al (2013) explore the effects of war-related violence on trust and cooperation in Tajikistan and found that exposure to war enhanced prosocial behavior.…”
Section: Insights From the Literaturementioning
confidence: 99%